Lived Experience of Women Applying for Divorce from Marital Life with a Husband Having Cluster B Personality Disorders: A Phenomenological Study - Aghajani, Somayeh; Haji Heydari, Mahnaz (Psychology of Woman Journal, 2026)
Objective: The objective of this study was to examine the interplay between developmental adversity, emotion dysregulation, interpersonal dysfunction, and psychotherapeutic interventions in explaining symptom persistence and change in borderline personality disorder.Methods and Materials: This study employed a structured analytical design integrating clinical, developmental, and therapeutic evidence related to borderline personality disorder. Data sources included standardized diagnostic frameworks, empirical findings on developmental risk factors, and outcome evidence from evidence-based psychotherapeutic approaches. Core domains of analysis encompassed early life adversity, affective instability, interpersonal functioning, comorbidity patterns, and treatment responsiveness, with particular attention to schema therapy, mentalization-based treatment, and integrative interventions grounded in contemporary clinical psychology.Findings: Inferential analysis indicated that childhood adversity and family instability were significantly associated with heightened affective instability and interpersonal dysfunction in borderline personality disorder. Emotion dysregulation emerged as a central mediating mechanism linking early relational trauma to adult symptom severity. Interpersonal dysfunction demonstrated robust associations with occupational impairment, relational instability, and psychosocial stress. Therapeutic findings suggested that structured psychotherapies, particularly schema-based and mentalization-oriented interventions, were associated with significant reductions in core borderline symptoms, while pharmacotherapy showed limited effects on core personality features and functioned primarily as an adjunct for comorbid conditions.Conclusion: The findings support an integrative, developmental–relational model of borderline personality disorder in which early adversity, emotion dysregulation, and interpersonal dysfunction jointly contribute to symptom persistence, while evidence-based psychotherapies offer meaningful pathways for clinical improvement. Emphasizing early intervention, trauma-informed care, and integrative therapeutic strategies may enhance long-term outcomes and reduce the individual and societal burden associated with borderline personality disorder.